Intraperitoneal Infusion of Mesenchymal Stem/Stromal Cells Prevents Experimental Autoimmune Uveitis in Mice - Joo Youn Oh; Tae Wan Kim; Hyun Jeong Jeong; Hyun Ju Lee; Jin Suk Ryu; Won Ryang Wee; Jang Won Heo; Mee Kum Kim (Mediators of Inflammation)
Autoimmune uveitis is one of the leading causes of blindness. We here investigated whether intraperitoneal administration of human mesenchymal stem/stromal cells (hMSCs) might prevent development of experimental autoimmune uveitis (EAU) in mice. Time course study showed that the number of IFN-γ- or IL-17-expressing CD4+ T cells was increased in draining lymph nodes (DLNs) on the postimmunization day 7 and decreased thereafter. The retinal structure was severely disrupted on day 21. An intraperitoneal injection of hMSCs at the time of immunization protected the retina from damage and suppressed the levels of proinflammatory cytokines in the eye. Analysis of DLNs on day 7 showed that hMSCs decreased the number of Th1 and Th17 cells. The hMSCs did not reduce the levels of IL-1β, IL-6, IL-12, and IL-23 which are the cytokines that drive Th1/Th17 differentiation. Also, hMSCs did not induce CD4+CD25+Foxp3+ cells. However, hMSCs increased the level of an immunoregulatory cytokine IL-10 and the population of IL-10-expressing B220+CD19+ cells. Together, data demonstrate that hMSCs attenuate EAU by suppressing Th1/Th17 cells and induce IL-10-expressing B220+CD19+ cells. Our results support suggestions that hMSCs may offer a therapy for autoimmune diseases mediated by Th1/Th17 responses.